Leaving prison: a multilevel investigation of racial, ethnic, and gender disproportionality in correctional release - Bradley-Engen, Mindy S. (Crime & delinquency, 2016)
Although the vast majority of people sent to prisons will eventually be released, we know relatively little about factors affecting correctional release. This study considers the roles of race, ethnicity, and gender in correctional release. Incorporating state-level predictors, including violent crime rates and sentencing policies, we examine variation in length of time served and the proportion of sentence incarcerated across demographics. Using National Corrections Reporting Program (NCRP) data, we determine the extent to which differences in time and proportion of sentence served is attributable to demographic and offending differences, as well as difference in sentencing and conditional release. Identifying race, ethnic, and gender disparities subsequent to court-ordered sentencing decisions has important implications for our understanding of justice and the salience of legal and extralegal factors across multiple phases of punishment.